2011
DOI: 10.1007/s10916-011-9718-x
|View full text |Cite
|
Sign up to set email alerts
|

Extracting Insights from Electronic Health Records: Case Studies, a Visual Analytics Process Model, and Design Recommendations

Abstract: Current electronic health record (EHR) systems facilitate the storage, retrieval, persistence, and sharing of patient data. However, the way physicians interact with EHRs has not changed much. More specifically, support for temporal analysis of a large number of EHRs has been lacking. A number of information visualization techniques have been proposed to alleviate this problem. Unfortunately, due to their limited application to a single case study, the results are often difficult to generalize across medical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 26 publications
0
42
0
Order By: Relevance
“…The characterization (▶ Table 2) of the visualization methods applied in the reviewed projects was based on the results and conclusions sections of the papers [24][25][26][27][28][30][31][32][33][34][35][36][37][38].…”
Section: Characterization Of the Visualization Methodsmentioning
confidence: 99%
“…The characterization (▶ Table 2) of the visualization methods applied in the reviewed projects was based on the results and conclusions sections of the papers [24][25][26][27][28][30][31][32][33][34][35][36][37][38].…”
Section: Characterization Of the Visualization Methodsmentioning
confidence: 99%
“…If an interface is designed such that the user can filter, arrange, and annotate the information in ways that facilitate the categorization task, the actions can be viewed as complementary. Empirical studies (e.g., [25][26][27][28][29][30]) suggest that complementary interactions can contribute positively towards performing diverse sensemaking activities with visualizations. For example, Groth and Streefkerk [26] found that allowing users to interact with 3D molecular visualizations, by rotating and annotating their elements, seemed to support users' performance of knowledge discovery tasks.…”
Section: Complementary Interactionsmentioning
confidence: 99%
“…Lifelines2 [23,24] aligns patient records by chosen events and can group patients by matching exact sequences of events. More sophisticated temporal queries (including temporal constraints and time spans between query elements) have been implemented in PatternFinder [25].…”
Section: Cohort Visualizationmentioning
confidence: 99%